A Study of Green Marketing in Sustainable Touris: The Perspective of Penglipuran Village, Bali, with Emphasis on Local Products - Ida Bagus Separsa Kusuma; I Putu Ari Utama Irawan (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This study aims to evaluate acceptance of Green Marketing strategies in Penglipuran Village, Bali, which is known with draft ecotourism and conservation culture. The main focus of this study is to measure visitors' perception of four Green Marketing indicators: Green Product, Green Price, Green Place, and Green Promotion. Research methods: Data obtained through questionnaire distributed to 57 respondents, with results analysis of validity and reliability that shows that all items in the instrument are valid and reliable. Results and discussions: The results of the validity test show r value count more than 0,30 to all items, with Green Product indicators obtained highest scores, followed by Green Place, Green Price, and Green Promotion. The results of the reliability test using Cronbach's Alpha show consistent values ​​between 0,754 and 0,899, with a total Cronbach's Alpha value of 0,818, indicating that the instrument is very reliable. Implication: Although in a way overall, acceptance towards Green Marketing in Penglipuran Village is in the "Good" category, there are a number of aspects that still need to be improved, such as environmentally friendly packaging, promotion of sustainability, and determination of environmentally friendly product prices.